Transcatheter Tricuspid Valve Replacement: Principles and Design - Demir, Ozan M.; Regazzoli, Damiano; Mangieri, Antonio; Ancona, Marco B.; Mitomo, Satoru; Weisz, Giora; Colombo, Antonio; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2018)
Tricuspid regurgitation (TR) may affect as much as 65-85% of the population with the prevalence of moderate-to-severe TR in the United States reported at greater than 1.6 million. However, only 8,000 tricuspid valve operations are performed annually in the United States. As severe TR is associated with poor outcomes, there is an unmet clinical need for surgical or percutaneous transcatheter based treatment of TR. Over the last two decades there have been significant developments in percutaneous transcatheter based therapies for valvular disease. However, this progress has not been mirrored for the tricuspid valve until recently; we are now at a cross-roads of new transcatheter devices becoming available for treatment of TR. In this review, we discuss the principles of performing transcatheter tricuspid valve replacement, analyze the devices that can be utilized and outline the challenges related to this procedure.